Effect of Age and Disease Duration on the Levodopa Response in Patients with Advanced Parkinson’s Disease for Deep Brain Stimulation of the Subthalamic Nucleus - Aygun, Dursun; Kocabicak, Ersoy; Yildiz, Mustafa Onur; Temel, Yasin (Frontiers in Neurology, 2016)
BACKGROUND: Deep brain stimulation (DBS) has become a preferred option for the treatment of motor symptoms in patients with advanced Parkinson’s disease (PD). A good levodopa response is considered the most important criterion in determining the suitability of a patient for DBS. However, the effect of age and disease duration on the levodopa response is still a subject of discussion. OBJECTIVE: Here, we investigated the effect of age and disease duration on the preoperative levodopa response in PD patients to be selected for DBS. METHODS: From August 2011 to May 2015, 54 consecutive patients (29 men and 25 women) with advanced PD were evaluated for DBS and included in this retrospective study. RESULTS: Thirty-seven patients were found suitable for subthalamic nucleus DBS and 29 of them underwent bilateral surgery. We found no significant correlation between disease duration and the levodopa response. However, there was a significant negative correlation between the patients’ age and the levodopa response. CONCLUSIONS: The results indicate that the patients’ age, rather than disease duration, has a negative effect on the levodopa response. The study therefore indicates that PD patients with an advanced age and with a poor levodopa response are not good candidates for subthalamic nucleus DBS.